STUDY ON ACCURACY OF BUILDING HEIGHT MEASUREMENT FROM SINGLE QUICKBIRD SATELLITE IMAGE FOR FORMING 3D CITY MODEL - Purwanto (NIM 25105030), Andi
ABSTRACT: Building height measurement needed to anticipates many high rise developments in urban area. PBB can apply result of building height measurement as reference of field verification activity and as data for forming 3d city model of PBB. PBB routinely purchase satellite image for updating of map PBB. These satellite images can also exploited for building height measurement. Building height measurement is done at single QuickBird satellite image with two methods that is direct measurement at building object in image by exploiting Rational Function Model (RFM) and through building shadow measurement of length. Research done to study accuracy of building height measurement from single QuickBird satellite image and determines best building height measurement method. Besides, this research also done to make three dimensions city model formed from building height data and length/wide building at single QuickBird satellite image. Building height measurement is done using SilverEye, software which can exploit Rational Polynomial Coefficient (RPC) QuickBird satellite image metadata. Direct building height measurement yields value RMSe 1,108 meter. Accuracy of building height measurement through building shadow length measurement is lower, with value RMSe 3,239 meter. Determinations of measurement point have a high influence in result of building altimetry. At building height measurement through length shadow measurement many influenced by something else like surface difference of tip of shadow and building base point and tip of shadow stays at other object. Building height measurement from single QuickBird satellite image hardly depend on existence of satellite image RPC metadata and there is building blocked by other building. But for building height measurement, this method is just requires single satellite image, practice, easy, and quick.